The burdens of disease : epidemics and human response in western history - Hays, J. N., 1938- (Rutgers University Press, 2009)
In this updated edition of The Burdens of Disease, with revisions and additions to the original content, including the evolution of drug-resistant diseases and expanded coverage of HIV/AIDS, along with recent data on mortality figures and other relevant statistics, J.N. Hays chronicles perceptions and responses to plague and pestilence over two thousand years of western history. Disease is framed as a multidimensional construct, situated at the intersection of history, politics, culture, and medicine, and rooted in mentalities and social relations as much as in biological conditions of p.